2022
DOI: 10.1186/s12891-022-06067-1
|View full text |Cite
|
Sign up to set email alerts
|

Medial meniscus posterior root tear reconstructed with gracilis autograft improve healing rate and patient reported outcome measures

Abstract: Background Many surgeries have not reversed or prevented progressive symptomatic knee arthritis, and there is no consensus regarding the ideal repair or reconstruction technique for meniscal root treatment. Additionally, there is a lack of studies comparing the clinical efficacy evaluation of different repair techniques. The aim of the present study is to compare the clinical efficacy and healing rates of meniscus root in the treatment of medial meniscus posterior root tear (MMPRT) with the art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…However, Chung et al reported that the K-L grade progressed in approximately 70% of patients at an average follow-up of 72 months after pull-out suturing [ 25 ]. Recently, MMPR-R has attracted significant attention [ 10 , 11 ]. Li et al compared MMPR-R and pull-out repair and reported that both the IKDC score and Lysholm score of patients who underwent MMPR-R significantly improved [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, Chung et al reported that the K-L grade progressed in approximately 70% of patients at an average follow-up of 72 months after pull-out suturing [ 25 ]. Recently, MMPR-R has attracted significant attention [ 10 , 11 ]. Li et al compared MMPR-R and pull-out repair and reported that both the IKDC score and Lysholm score of patients who underwent MMPR-R significantly improved [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, MMPR-R has attracted significant attention [ 10 , 11 ]. Li et al compared MMPR-R and pull-out repair and reported that both the IKDC score and Lysholm score of patients who underwent MMPR-R significantly improved [ 10 ]. In addition, Kim et al revealed that a varus knee alignment of > 5° requires alignment correction [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations